Early targeted brain COOLing in the cardiac CATHeterisation laboratory following cardiac arrest (COOLCATH). (December 2015) - Islam, Shahed; Hampton-Till, James; Watson, Noel; Mannakkara, Nilanka N.; Hamarneh, Ashraf; Webber, Teresa; Magee, Neil; Abbey, Lucy; Jagathesan, Rohan; Kabir, Alamgir; Sayer, Jeremy; Robinson, Nicholas; et al.
Abstract: Introduction: Trials demonstrate significant clinical benefit in patients receiving therapeutic hypothermia (TH) after cardiac arrest. However, incidence of mortality and morbidity remains high in this patient group. Rapid targeted brain hypothermia induction, together with prompt correction of the underlying cause may improve outcomes in these patients. This study investigates the efficacy of Rhinochill ®, an intranasal cooling device over Blanketrol ®, a surface cooling device in inducing TH in cardiac arrest patients within the cardiac catheter laboratory. Methods: 70 patients were randomized to TH induction with either Rhinochill ® or Blanketrol ® . Primary outcome measures were time to reach tympanic ≤34 °C from randomisation as a surrogate for brain temperature and oesophageal ≤34 °C from randomisation as a measurement of core body temperature. Secondary outcomes included first hour temperature drop, length of stay in intensive care unit, hospital stay, neurological recovery and all-cause mortality at hospital discharge. Results: There was no difference in time to reach ≤34 °C between Rhinochill ® and Blanketrol ® (Tympanic ≤34 °C, 75 vs. 107 mins; p = 0.101; Oesophageal ≤34 °C, 85 vs. 115 mins; p = 0.151). Tympanic temperature dropped significantly with Rhinochill ® in the first hour (1.75 vs. 0.94 °C; p < 0.001). No difference was detected in any other secondary outcome measures. Catheter laboratory-based TH induction resulted in a survival to hospital discharge of 67.1%. Conclusion: In this study, Rhinochill ® was not found to be more efficient than Blanketrol ® for TH induction, although there was a non-significant trend in favour of Rhinochill ® that potentially warrants further investigation with a larger trial.